2019
DOI: 10.1001/jamaophthalmol.2019.1318
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Novel Genome-Wide Significant Gene Loci and Lesion Growth in Geographic Atrophy Secondary to Age-Related Macular Degeneration

Abstract: IMPORTANCE Age-related macular degeneration (AMD) is a common threat to vision loss in individuals older than 50 years. While neovascular complications in AMD are treatable, there is currently no therapy for geographic atrophy secondary to AMD. Geographic atrophy lesion progression over time shows considerable interindividual variability, but little is known about prognostic factors. OBJECTIVE To elucidate the contribution of common genetic variants to geographic atrophy lesion growth. DESIGN, SETTING, AND PAR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 50 publications
0
26
0
Order By: Relevance
“…A 2019 genome-wide association study found novel SNPs specifically associated with GA enlargement: variants in PRMT6 (rs11184959) and LSS (rs2839127). 33 Jointly, these SNPs explained only 6% of the variation in GA enlargement.…”
Section: Discussionmentioning
confidence: 97%
“…A 2019 genome-wide association study found novel SNPs specifically associated with GA enlargement: variants in PRMT6 (rs11184959) and LSS (rs2839127). 33 Jointly, these SNPs explained only 6% of the variation in GA enlargement.…”
Section: Discussionmentioning
confidence: 97%
“…23 Currently there is no approved treatment to halt/restore degenerative changes caused by GA. Several genes have been found to show promise as being potential targets for gene therapy as well. 24,25 The success of future gene therapies and advanced rehabilitative therapies depend on the understanding of retinal structural changes, and quantitative analysis of retinal layers can help increase our understanding of the disease as well as reveal potential targets for treatment or intervention. It may also provide a way to objectively measure clinical response and outcomes of future therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Downstream of C3 cleavage, C3 fragments exert a variety of effector functions and C5 initiates membrane attack complex formation 9 . Assuming that the complement system also impacts GA progression rates (a so-far unproven hypothesis in the natural-history setting) 10 12 , multiple complement inhibitors are currently evaluated in clinical trials aiming to slow GA progression. These include pegcetacoplan (APL-2), which slowed GA progression in recent Phase 2 and 3 trials 13 – 15 .…”
Section: Introductionmentioning
confidence: 99%